Sisymbrium isatidifolium (Brassicaceae): a new species from southern Spain, and the identity of S. hispanicum Jacq. - Blanca, Gabriel; Cueto, Miguel; Fuentes, Julián (Phytotaxa, 2015)
A new species of the genus Sisymbrium is described, illustrated, and compared with the most closely related ones of the genus, S. chrysanthum, S. hispanicum, S. crassifolium, and S. assoanum, and the identity of S. hispanicum is discussed. The new species occurs on gypsiferous marls, forming part of the esparto grasslands and cultivated fields in the provinces of Albacete, Jaén, Granada, and Almería (southern Spain). In addition, a distribution map, illustrations, and a description of the habitat of the new species are presented.